Titanium oxide, powder, powder composition, solid composition, liquid composition, and molded body

JP7609563B2Active Publication Date: 2025-01-07SUMITOMO CHEM CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020063973
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-03-31
Publication Date
2025-01-07
Estimated Expiration
2040-03-31

AI Technical Summary

Benefits of technology

【0017】 本発明によれば、比較的低い温度域において最大の絶対値の負の熱線膨張係数を有する材料を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007609563000003
    Figure 0007609563000003
  • Figure 0007609563000004
    Figure 0007609563000004
  • Figure 0007609563000005
    Figure 0007609563000005
Patent Text Reader

Abstract

To provide a material having a maximum absolute value negative thermal coefficient of linear expansion in a comparatively low temperature range.SOLUTION: A titanium oxide satisfies the following requirements 1-3. Requirement 1: A(T) is less than 0.3780 at T=25°C where A(T) is (a lattice constant of an a-axis (short axis) of the titanium oxide) / (a lattice constant of a c-axis (long axis) of the titanium oxide) at a temperature T, and the lattice constants are obtained by X-ray diffraction measurement of the titanium oxide. Requirement 2: a metal other than titanium and / or a metalloid element are / is contained. Requirement 3: the total mol content of the metal other than titanium and the metalloid element is a mol content of titanium or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a titanium oxide, a powder, a powder composition, a solid composition, a liquid composition, and a molded body. [Background technology]

[0002] It is known that in order to reduce the coefficient of linear thermal expansion of a solid composition, a filler having a small value of the coefficient of linear thermal expansion is added.

[0003] For example, Patent Document 1 discloses tungsten zirconium phosphate as a filler material exhibiting a negative coefficient of linear thermal expansion. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2018-2577 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, in conventional materials, the coefficient of linear thermal expansion is not necessarily reduced sufficiently.

[0006] In addition, it is important for applications that the coefficient of linear thermal expansion can be controlled according to the temperature range used for each application. For example, since resin materials for semiconductor encapsulation are generally used at 200°C or less, it is preferable for a material to have a large absolute negative coefficient of linear thermal expansion at 200°C or less when added to a resin material for semiconductor encapsulation. In particular, if it is possible to adjust the temperature at which the material has the maximum absolute negative coefficient of linear thermal expansion, it becomes possible to design a composite material having a coefficient of linear thermal expansion according to the application by adjusting the amount of the material added.

[0007] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a material having a negative coefficient of linear thermal expansion with a maximum absolute value in a relatively low temperature range. [Means for solving the problem]

[0008] As a result of extensive investigations, the present inventors have arrived at the present invention. That is, the present invention provides the following.

[0009] The titanium oxide according to the present invention satisfies the following requirements 1 to 3. Requirement 1: A(T) is less than 0.3780 at T = 25°C. A(T) is (a-axis (short axis) lattice constant of the titanium oxide) / (c-axis (long axis) lattice constant of the titanium oxide) at temperature T, and each of the lattice constants is obtained from X-ray diffraction measurement of the titanium oxide. Requirement 2: Contains metal and / or metalloid elements other than titanium. Requirement 3: The total molar content of metal and metalloid elements other than titanium is less than or equal to the molar content of titanium.

[0010] Here, A(T) in requirement 1 above can be 0.3774 or less at T=25°C.

[0011] The metal and / or metalloid element other than titanium can be selected from the group of elements belonging to the third to sixth periods.

[0012] The powder according to the present invention is the titanium oxide powder.

[0013] The powder composition according to the present invention contains the above powder.

[0014] The solid composition according to the present invention contains the above-mentioned powder or the above-mentioned powder composition.

[0015] The liquid composition according to the present invention contains the above powder or the above powder composition.

[0016] The molded article according to the present invention is a molded article of the above powder or the above powder composition. Effect of the Invention

[0017] According to the present invention, it is possible to provide a material having a negative coefficient of linear thermal expansion with a maximum absolute value in a relatively low temperature range. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is a graph showing the temperature dependence of the dimensional change rate ΔL(T) / L (30° C.) in Examples 1, 2 and 5 and Comparative Examples 1, 2 and 3. [Diagram 2] FIG. 2 is a graph showing the coefficient of linear thermal expansion α(T) (1 / ° C.) of Examples 1 to 5 and Comparative Examples 1, 2 and 3, that is, the temperature derivative of the dimensional change ΔL(T) / L (30° C.). [Diagram 3] FIG. 3 is a graph showing the relationship between temperature and A(T) in Examples 1 and 5 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Preferred embodiments of the present invention will be described in detail below, however, the present invention is not limited to the following embodiments.

[0020] <Titanium oxide> The titanium oxide according to the present invention satisfies the following requirements 1 to 3.

[0021] Requirement 1: A(T) is less than 0.3780 at T = 25°C. A(T) is (a-axis (short axis) lattice constant of the titanium oxide) / (c-axis (long axis) lattice constant of the titanium oxide) at temperature T, and each of the lattice constants is obtained from X-ray diffraction measurement of the titanium oxide.

[0022] Requirement 2: Contains metal and / or metalloid elements other than titanium.

[0023] Requirement 3: The total molar content of metal and metalloid elements other than titanium is less than or equal to the molar content of titanium.

[0024] The lattice constants in the definition of A(T) are determined by powder X-ray diffraction measurements. Analysis methods include the Rietveld method and least-squares fitting.

[0025] In this specification, the axis corresponding to the smallest lattice constant in the crystal structure determined by powder X-ray diffraction measurement is defined as the a-axis, and the axis corresponding to the largest lattice constant is defined as the c-axis. The lengths of the a-axis and c-axis of the crystal lattice are defined as the a-axis length and the c-axis length, respectively.

[0026] A(T) is a parameter that indicates the magnitude of anisotropy of the crystal axis length at temperature T. The larger the value of A, the larger the a-axis length relative to the c-axis length, and the smaller the value of A, the smaller the a-axis length relative to the c-axis length.

[0027] The value of A(T) at T=25° C. of the titanium oxide of the present invention is less than 0.3780, preferably 0.3778 or less, more preferably 0.3776 or less, even more preferably 0.3774 or less, and even more preferably 0.3772 or less. By being in this range, the temperature at which the maximum absolute value of the negative linear thermal expansion coefficient is obtained can be effectively lowered.

[0028] The lower limit of the value of A(T) at T=25° C. is preferably 0.3500 or more, more preferably 0.3600 or more, and further preferably 0.3710 or more. By being in this range, the structural stability is increased, resulting in a thermally stable structure.

[0029] Furthermore, the value of A(T) at T=100° C. is preferably 0.3780 or less, more preferably 0.3769 or less, and even more preferably 0.3765 or less. By being in this range, the temperature at which the absolute value of the negative linear thermal expansion coefficient is the maximum can be effectively lowered.

[0030] The lower limit of the value of A(T) at T=100° C. is preferably 0.3500 or more, more preferably 0.3600 or more, and further preferably 0.3710 or more. By being in this range, the structural stability is increased, resulting in a thermally stable structure.

[0031] Depending on the type of titanium oxide crystal, the crystal structure changes due to a structural phase transition in a specific temperature range. In this specification, in the crystal structure at a certain temperature T, the axis with the largest crystal lattice constant is the c-axis, and the axis with the smallest crystal lattice constant is the a-axis. In any crystal system, including triclinic, monoclinic, orthorhombic, tetragonal, hexagonal, and rhombohedral, the a-axis and c-axis are defined as above.

[0032] The titanium oxide of the present invention contains a metal and / or a metalloid element other than titanium, that is, the titanium oxide may contain one or more metal elements other than titanium, may contain one or more metalloid elements, or may contain a combination of one or more metal elements other than titanium and one or more metalloid elements.

[0033] The metal and / or metalloid element other than titanium contained in the titanium oxide of the present invention is preferably selected from the group of elements belonging to Periods 3 to 6, and more preferably from the group of elements belonging to Periods 3 to 5. By selecting from this group of elements, a thermally stable compound can be obtained.

[0034] From the viewpoint of effectively lowering the temperature having the maximum absolute negative linear thermal expansion coefficient, the elements belonging to the third period are preferably Mg and Al, the elements belonging to the fourth period are preferably Ca, Sc, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, and Ge, the elements belonging to the fifth period are preferably Sr, Y, Zr, Nb, Mo, In, Sn, Sb, and Te, and the elements belonging to the sixth period are preferably Cs, Ba, La, Ce, Pr, Nd, W, and Bi. In particular, Al, Sc, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Zr, Nb, Mo, and Sb are preferable, and among them, Al, Cr, and Nb are preferable.

[0035] The total molar content of metal and metalloid elements other than titanium in the titanium oxide of the present invention is equal to or less than the molar content of titanium.

[0036] From the viewpoint of exhibiting a large absolute value of a negative coefficient of linear thermal expansion, the total molar content of metal and metalloid elements other than titanium in the titanium oxide of the present invention is preferably 50% or less of the molar content of titanium, more preferably 30% or less, even more preferably 20% or less, and particularly preferably 15% or less.

[0037] Furthermore, from the viewpoint of effectively lowering the temperature having the maximum absolute value of the negative linear thermal expansion coefficient, the total molar content of metal and metalloid elements other than titanium in the titanium oxide of the present invention is preferably greater than 0.5% of the molar content of titanium, and is preferably 1% or more, more preferably 3% or more, and even more preferably 5% or more.

[0038] The titanium oxide of the present invention preferably has a corundum structure, which makes it possible to exhibit a large absolute negative coefficient of linear thermal expansion.

[0039] The crystal system is not particularly limited, but it is preferably a rhombohedral system because it allows the crystal to exhibit a large absolute negative coefficient of linear thermal expansion.The space group is preferably R-3c.

[0040] The titanium oxide of the present invention has the composition formula Ti 2-x M x O 3-δ (x=0.02 to 0.66, δ=-0.32 to 0.40), and Ti 2-x M x O 3-δ (x=0.06 to 0.40, δ=-0.20 to 0.20), and Ti 2-x M x O 3-δ(x=0.10 to 0.30, δ=−0.10 to 0.10) is particularly preferred, where M represents a metal and / or semimetal element other than titanium. When x and δ are within the above ranges, the titanium oxide of the present invention has improved thermal stability and a large absolute value of the negative thermal expansion coefficient. When M contains two or more elements selected from the group consisting of metals and metalloid elements other than titanium, the subscript x of M indicates the molar ratio of the total of these elements. When M contains two or more elements, there is no particular limitation on the molar ratio between each element of M.

[0041] In the present invention, the δ represents the amount of oxygen vacancy in titanium oxide, and can be calculated by a thermogravimetric analysis test. The method for measuring the amount of oxygen vacancy δ by thermogravimetric analysis is described below. Titanium oxide is heated and oxidized under a flow of dry air until there is no substantial weight increase. δ can be calculated based on the weight increase until the end of heating. For example, a thermogravimetric analyzer TGDTA6300AST-2 (manufactured by SII NanoTechnology Co., Ltd.) can be used as a measuring device.

[0042] According to the titanium oxide according to this embodiment, the temperature at which the maximum absolute value of the negative thermal expansion coefficient is exhibited can be made relatively low, for example, less than 190° C., 180° C. or less, or 175° C. or less. According to the titanium oxide of this embodiment, the maximum absolute value of the negative thermal expansion coefficient can be set to -5 ppm / °C or less, -10 ppm / °C or less, -15 ppm / °C or less, -20 ppm / °C or less, or -25 ppm / °C or less.

[0043] The titanium oxide of the present invention may be in the form of a powder. This powder can be suitably used as a filler to be added to a solid composition in order to control the thermal expansion coefficient of the solid composition.

[0044] The D90 of the titanium oxide powder is preferably 0.5 μm or more and 70 μm or less. The D90 is preferably 0.6 μm or more, and more preferably 0.7 μm or more. The D90 is preferably 60 μm or less, and more preferably 40 μm or less. When the D90 is in such a range, the coating property is improved. When the D90 is 0.5 μm or more, agglomerates are unlikely to be formed, and the uniformity when kneaded with a matrix material such as a resin is likely to be improved. The D50 is preferably 0.5 μm or more and 60 μm or less. When the D50 is 60 μm or less, the coating property tends to be improved. When the D50 is 0.5 μm or more, agglomerates are unlikely to be formed, and the uniformity when kneaded with a matrix material such as a resin is likely to be improved.

[0045] In this specification, D50 and D90 refer to the particle size at which the cumulative frequency is 50% when the cumulative frequency is calculated from the smaller particle size in a volume-based cumulative particle size distribution curve obtained by a laser diffraction scattering method, and D50 is the particle size at which the cumulative frequency is 90%, and D90 is the particle size at which the cumulative frequency is 90%. The particle size distribution based on volume is measured by a laser diffraction scattering method. For example, a laser diffraction particle size distribution measuring device, Mastersizer 2000, manufactured by Malvern Instruments Ltd., can be used. The refractive index is set to 2.40.

[0046] The BET specific surface area of ​​the titanium oxide powder of the present invention is 0.1 m 2 / g or more 20.0m 2 It is preferable that the molecular weight is not more than 1 / g.

[0047] <Method of manufacturing titanium oxide and its powder> There is no particular limitation on the method for producing the titanium oxide of the present invention. For example, it can be obtained by sintering a raw material powder of titanium oxide. There is no particular limitation on the sintering method, and it may be a normal pressure sintering method using a heating device such as an electric furnace, a hot press method or a hot isostatic sintering (HIP) method in which heating is performed while applying pressure, or a spark plasma sintering method in which electrical heating is performed while applying pressure. In particular, the spark plasma sintering method is preferable.

[0048] In the spark plasma sintering, a pulsed current is passed through the mixture of raw materials for the titanium oxide of the present invention while pressurizing the mixture, which generates an electric discharge in the raw material mixture and allows the mixture to be heated and sintered.

[0049] In order to prevent the resulting compound from being altered by contact with air, the plasma sintering step is preferably carried out in an inert atmosphere such as argon, nitrogen, or vacuum.

[0050] The pressure applied in the plasma sintering step is preferably in the range of more than 0 MPa and not more than 100 MPa. In order to obtain a high-density first material, the pressure applied in the plasma sintering step is preferably 10 MPa or more, more preferably 30 MPa or more. The heating temperature in the plasma sintering step is preferably sufficiently lower than the melting point of the target titanium oxide.

[0051] The raw powder includes a titanium source, a metal and / or metalloid source other than titanium, and an oxygen source. Examples of the titanium source are titanium oxides such as Ti2O3 and TiO2, and metallic titanium. Examples of the metal and / or metalloid source other than titanium are oxides, hydroxides, and simple substances of metal and / or metalloid elements other than titanium. The oxygen source is usually titanium oxide or an oxide of a metal and / or metalloid element other than titanium. That is, it is preferable that at least one of the titanium source and the metal and / or metalloid source other than titanium is an oxide, and more preferably, both are oxides. When the titanium source and / or the metal and / or metalloid source other than titanium are oxides, each may be entirely an oxide, or each may be partially an oxide and the remaining portion may be a non-oxide such as a metal. This makes it possible to control the ratio of oxygen in the product, that is, δ in the above formula. In addition, by adjusting the molar content of titanium in the raw powder and the ratio of the content of the metal and / or metalloid element other than titanium, x in the above formula can be adjusted in the obtained titanium oxide.

[0052] The plasma sintering process may be divided into two stages. That is, the spark plasma sintering may be performed in the following manner. By performing such two-stage spark plasma sintering, impurity phases can be removed and metal and / or semimetal elements other than titanium can be more easily dissolved, which is preferable.

[0053] First, a first mixing step is performed in which a titanium oxide is mixed with a metal and / or metalloid source other than titanium to obtain a first mixed powder, followed by a first spark plasma sintering step in which the first mixed powder is subjected to spark plasma sintering to obtain a first sintered body. Next, the first sintered body thus obtained is pulverized, and then metallic titanium and a metal and / or metalloid source other than titanium are mixed therewith to obtain a second mixed powder in a second mixing step, after which the second mixed powder is subjected to spark plasma sintering to obtain a second sintered body in a second spark plasma sintering step.

[0054] The resulting titanium oxide lumps are then crushed, sieved, pulverized, or otherwise adjusted to adjust the particle size distribution, thereby obtaining titanium oxide powder.

[0055] <Powder composition containing titanium oxide powder> One embodiment of the present invention is a powder composition containing the titanium oxide powder and other powders, and the powder composition is a powdery composition. Such a powder composition can be suitably used as a filler for controlling the thermal expansion coefficient of a solid composition described later. There is no limitation on the content of titanium oxide in the powder composition, and the powder composition can exert a function of controlling the amount of thermal expansion depending on the content. From the viewpoint of efficiently controlling the amount of thermal expansion, the content of the titanium oxide may be 75% by mass or more, 85% by mass or more, or 95% by mass or more.

[0056] Examples of powders in the powder composition other than the titanium oxide powder include calcium carbonate, talc, mica, silica, clay, wollastonite, potassium titanate, xonotlite, gypsum fiber, aluminum borate, aramid fiber, carbon fiber, glass fiber, glass flakes, polyoxybenzoyl whiskers, glass balloons, carbon black, graphite, alumina, aluminum nitride, boron nitride, beryllium oxide, ferrite, iron oxide, barium titanate, lead zirconate titanate, zeolite, iron powder, aluminum powder, barium sulfate, zinc borate, red phosphorus, magnesium oxide, hydrotalcite, antimony oxide, aluminum hydroxide, magnesium hydroxide, zinc carbonate, TiO2, and TiO.

[0057] The D90, D50 and BET specific surface area of ​​the powder composition can be set in the same manner as the D90 and D50 of the titanium oxide powder described above.

[0058] The method for producing the powder composition is not particularly limited, but for example, the above-mentioned titanium oxide powder may be mixed with other fillers, and the particle size distribution may be adjusted as necessary by crushing, sieving, grinding, or the like.

[0059] <Molded body> The molded body according to this embodiment is a molded body of the above-mentioned titanium oxide powder or powder composition. The molded body according to this embodiment may be a sintered body obtained by sintering the titanium oxide powder or powder composition.

[0060] Generally, the above powder or powder composition is sintered to obtain a molded body. In this case, it is preferable to carry out the sintering within a temperature range in which the crystal structure of titanium oxide is maintained.

[0061] To obtain a sintered body, various known sintering methods can be used, such as ordinary heating, hot pressing, the above-mentioned spark plasma sintering, etc.

[0062] The heating temperature for plasma sintering is preferably sufficiently lower than the melting point of titanium oxide.

[0063] The molded body according to this embodiment is not limited to a sintered body, and may be, for example, a green compact obtained by pressure molding of a powder or a powder composition.

[0064] According to the powder or the molded product of the powder composition of the present embodiment, a member having little thermal expansion can be provided, and the dimensional change of the member when the temperature changes can be made extremely small. Therefore, it can be suitably used for various members used in devices that are particularly sensitive to dimensional changes due to temperature.

[0065] In addition, by combining the powder or the molded body of the powder composition with another material having a positive linear thermal expansion coefficient, the linear thermal expansion coefficient of the entire member can be controlled to be low. For example, by using the molded body of the powder of this embodiment in a part of the length direction of a bar material and using a material having a positive linear thermal expansion coefficient in the other part, the linear thermal expansion coefficient in the length direction of the bar material can be freely controlled according to the ratio of the two materials. For example, it is possible to make the thermal expansion of the bar material in the length direction substantially zero.

[0066] <Solid composition> The solid composition according to this embodiment contains the above-mentioned titanium oxide powder or powder composition and a first material.

[0067] [First ingredient] The first material is not particularly limited, but may include resin, alkali metal silicate, ceramics, metal, etc. The first material may be a binder material that bonds the titanium oxides together, or a matrix material that holds the titanium oxides in a dispersed state.

[0068] Examples of the resin include thermoplastic resins and cured products of heat- or active energy ray-curable resins.

[0069] Examples of the thermosetting resin include epoxy resin, oxetane resin, unsaturated polyester resin, alkyd resin, phenolic resin (novolac resin, resol resin, etc.), acrylic resin, urethane resin, silicone resin, polyimide resin, and melamine resin. Examples of active energy ray curable resins include ultraviolet ray curable resins and electron beam curable resins, such as urethane acrylate resins, epoxy acrylate resins, acrylic acrylate resins, polyester acrylate resins, and phenol methacrylate resins.

[0070] Examples of thermoplastic resins include polyolefins (polyethylene, polypropylene, etc.), ABS resins, polyamides (nylon 6, nylon 6,6, etc.), polyamideimides, polyesters (polyethylene terephthalate, polyethylene naphthalate), liquid crystal polymers, polyphenylene ethers, polyacetals, polycarbonates, polyphenylene sulfides, polyimides, polyetherimides, polyethersulfones, polyketones, polystyrenes, and polyetheretherketones.

[0071] The first material may contain one type of the above resin, or may contain two or more types of the above resin.

[0072] From the viewpoint of increasing heat resistance, the first material is preferably an epoxy resin, polyethersulfone, a liquid crystal polymer, polyimide, polyamideimide, or silicone.

[0073] Examples of alkali metal silicates include lithium silicate, sodium silicate, and potassium silicate. The first material may contain one type of alkali metal silicate, or may contain two or more types. These materials are preferred because they have high heat resistance.

[0074] The ceramics are not particularly limited, but include oxide ceramics such as alumina, silica (including silicon oxide and silica glass), titania, zirconia, magnesia, ceria, yttria, zinc oxide, and iron oxide; nitride ceramics such as silicon nitride, titanium nitride, and boron nitride; and ceramics such as silicon carbide, calcium carbonate, aluminum sulfate, barium sulfate, aluminum hydroxide, potassium titanate, talc, kaolin clay, kaolinite, halloysite, pyrophyllite, montmorillonite, sericite, mica, amesite, bentonite, asbestos, zeolite, calcium silicate, magnesium silicate, diatomaceous earth, and silica sand. The first material may contain one type of ceramic, or two or more types. Ceramics are preferred because they have high heat resistance, and sintered bodies can be made by spark plasma sintering or the like.

[0075] The metal is not particularly limited, but may be an elemental metal such as aluminum, tantalum, niobium, titanium, molybdenum, iron, nickel, cobalt, chromium, copper, silver, gold, platinum, lead, tin, tungsten, or the like, an alloy such as stainless steel (SUS), or a mixture thereof. The first material may contain one type of metal or two or more types of metal. Such metals are preferable because they can provide high heat resistance.

[0076] [Other ingredients] The solid composition may contain other components than the first material and the titanium oxide powder or powder composition. For example, a catalyst may be used. The catalyst is not particularly limited, but may be an acidic compound, an alkaline compound, or an organometallic compound. The acidic compound may be an acid such as hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, formic acid, acetic acid, or oxalic acid. The alkaline compound may be ammonium hydroxide, tetramethylammonium hydroxide, or tetraethylammonium hydroxide. The organometallic compound catalyst may be one containing aluminum, zirconium, tin, titanium, or zinc.

[0077] The content of titanium oxide in the solid composition is not particularly limited, and the function of controlling thermal expansion can be exerted according to the content. The content of titanium oxide in the solid composition can be, for example, 1% by weight or more, 3% by weight or more, 5% by weight or more, 10% by weight or more, 20% by weight or more, 40% by weight or more, or 70% by weight or more. When the content of titanium oxide is high, the effect of reducing the linear thermal expansion coefficient is easily exerted. The content of titanium oxide in the solid composition can be, for example, 99% by weight or less. The content of titanium oxide in the solid composition can be 95% by weight or less, or 90% by weight or less.

[0078] The content of the first material in the solid composition can be, for example, 1% by weight or more. The content of the first material in the solid composition can be, for example, 5% by weight or more, or 10% by weight or more. The content of the first material in the solid composition can be, for example, 99% by weight or less. The content of the first material in the solid composition can be, for example, 97% by weight or less, 95% by weight or less, 90% by weight or less, 80% by weight or less, 60% by weight or less, or 30% by weight or less.

[0079] The solid composition according to the present embodiment contains the titanium oxide according to the present embodiment, and thus has a sufficiently low coefficient of linear thermal expansion. This solid composition can provide a member that exhibits extremely little dimensional change when the temperature changes. Therefore, the solid composition can be suitably used for optical members and semiconductor manufacturing equipment members that are particularly sensitive to dimensional changes due to temperature.

[0080] In particular, since the absolute value of the maximum negative thermal expansion coefficient of the titanium oxide is sufficiently large, a solid composition (material) having a negative linear thermal expansion coefficient can be obtained. Having a negative linear thermal expansion coefficient means that the volume shrinks with linear thermal expansion. In a plate in which an end face (side face) of a plate of a solid composition having a negative linear thermal expansion coefficient is joined to an end face of a plate of another material having a positive linear thermal expansion coefficient, the linear thermal expansion coefficient of the entire plate in the direction perpendicular to the thickness direction can be made substantially zero.

[0081] Furthermore, the temperature at which the titanium oxide exhibits the maximum absolute negative thermal expansion coefficient can be made relatively low, for example, less than 190° C. Therefore, the thermal expansion coefficient of the solid composition can be made small in a temperature range less than 190° C. Also, by adding both the titanium oxide powder and a material that exhibits the maximum absolute negative thermal expansion coefficient at around 200° C., such as Ti2O3, to the solid composition, the thermal expansion coefficient of the solid composition can be made low over a wide temperature range, which is preferable.

[0082] <Liquid composition> The liquid composition according to this embodiment contains the titanium oxide powder or powder composition and a second material. The liquid composition has fluidity at 25° C. This liquid composition can be a raw material for the solid composition.

[0083] [Second ingredient] The second material may be in a liquid state and capable of dispersing the titanium oxide powder or powder composition. The second material may be a raw material for the first material.

[0084] For example, when the first material is an alkali metal silicate, the second material may include an alkali metal silicate and a solvent capable of dissolving or dispersing the alkali metal silicate. When the first material is a thermoplastic resin, the second material may include a thermoplastic resin and a solvent capable of dissolving or dispersing the thermoplastic resin. When the first material is a cured product of a heat- or active energy ray-curable resin, the second material is a heat- or active energy ray-curable resin before curing.

[0085] The thermosetting resin before curing has fluidity at room temperature, and when heated, it cures by a crosslinking reaction, etc. The thermosetting resin before curing may contain one type of resin or may contain two or more types of resin.

[0086] The active energy ray curable resin before curing has fluidity at room temperature, and is cured by irradiation with active energy rays such as light (UV, etc.) or electron beams, etc., through a crosslinking reaction or the like. The active energy ray curable resin before curing contains a curable monomer and / or a curable oligomer, and may further contain a solvent and / or a photoinitiator, as necessary. Examples of the curable monomer and the curable oligomer are a photocurable monomer and a photocurable oligomer. Examples of the photocurable monomer are a monofunctional or polyfunctional acrylate monomer. Examples of the photocurable oligomer are urethane acrylate, epoxy acrylate, acrylic acrylate, polyester acrylate, and phenol methacrylate.

[0087] Examples of the solvent include organic solvents such as alcohol solvents, ether solvents, ketone solvents, glycol solvents, hydrocarbon solvents, and aprotic polar solvents, and water. In the case of an alkali metal silicate, the solvent is, for example, water.

[0088] [Other ingredients] The liquid composition of the present embodiment may contain other components in addition to the second material and the titanium oxide powder or powder composition, for example, the other components listed for the first material.

[0089] The content of titanium oxide in the liquid composition is not particularly limited, and can be appropriately set from the viewpoint of controlling the thermal expansion amount of the solid composition after curing. Specifically, it can be the same as that of the first material.

[0090] <Method of producing liquid composition> The method for producing the liquid composition is not particularly limited. For example, the liquid composition can be obtained by stirring and mixing the above-mentioned titanium oxide powder or powder composition with the second material. As a stirring method, for example, stirring with a mixer can be mentioned. Alternatively, the titanium oxide can be dispersed in the second material by ultrasonic treatment.

[0091] Examples of the mixing method used in the mixing step include a ball mill method, a rotation / revolution mixer, an impeller rotation method, a blade rotation method, a rotating thin film method, a rotor / stator mixer method, a colloid mill method, a high-pressure homogenizer method, and an ultrasonic dispersion method. In the mixing step, a plurality of mixing methods may be performed in order or simultaneously. In the mixing step, the composition is homogenized and shear is applied to the composition, thereby increasing the fluidity and deformability of the composition.

[0092] <Method of producing solid composition> After the above liquid composition is molded into a desired shape, the second material in the liquid composition is converted into the first material, thereby producing a solid composition in which titanium oxide and the first material are composited.

[0093] For example, when the second material contains an alkali metal silicate and a solvent capable of dissolving or dispersing the alkali metal silicate, and contains a thermoplastic resin and a solvent capable of dissolving or dispersing the thermoplastic resin, the liquid composition can be formed into the desired shape and then the solvent can be removed from the liquid composition to obtain a solid composition containing titanium oxide and the first material (alkali metal salt or thermoplastic resin).

[0094] The solvent can be removed by evaporating the solvent through natural drying, vacuum drying, heating, etc. From the viewpoint of suppressing the generation of coarse bubbles, it is preferable to remove the solvent while maintaining the temperature of the mixture at or below the boiling point of the solvent.

[0095] When the second material is a heat or active energy ray curable resin, the liquid composition may be formed into a desired shape and then cured with heat or active energy rays (UV, etc.).

[0096] Examples of methods for forming the liquid composition into a desired shape include pouring it into a mold and spreading it onto a substrate surface in the form of a film.

[0097] In addition, when the first material is a ceramic or metal, the following method can be used. A mixture of raw powder of the first material and titanium oxide is prepared, and the mixture is heat-treated to sinter the raw powder of the first material, thereby obtaining a solid composition containing the first material and titanium oxide as a sintered body. If necessary, the pores of the solid composition can be adjusted by heat treatment such as annealing. As a sintering method, methods such as normal heating, hot pressing, and discharge plasma sintering can be used.

[0098] In spark plasma sintering, a mixture of raw material powder of a first material and titanium oxide is pressurized while a pulsed current is passed through the mixture, which generates an electric discharge between the raw material powder of the first material, heating and sintering the raw material powder of the first material.

[0099] In order to prevent the resulting compound from being altered by contact with air, the plasma sintering step is preferably carried out in an inert atmosphere such as argon, nitrogen, or vacuum.

[0100] The pressure applied in the plasma sintering step is preferably in the range of more than 0 MPa to 100 MPa or less. In order to obtain a high-density first material, the pressure applied in the plasma sintering step is preferably 10 MPa or more, and more preferably 30 MPa or more.

[0101] The heating temperature in the plasma sintering step is preferably sufficiently lower than the melting point of the first material, which is the target object.

[0102] Furthermore, the size and distribution of the pores can be adjusted by heat treating the resulting solid composition. EXAMPLES

[0103] The present invention will now be described in more detail with reference to examples.

[0104] <Crystal structure analysis of titanium oxide> To analyze the crystal structure, the powder was subjected to powder X-ray diffraction measurement at different temperatures under the following conditions using a powder X-ray diffraction measuring device SmartLab (manufactured by Rigaku Corporation) to obtain powder X-ray diffraction patterns. Based on the obtained patterns, the lattice constants were refined by the least squares method using PDXL2 (manufactured by Rigaku Corporation) software, and the a-axis lattice constant and c-axis lattice constant were obtained in the range of 25°C to 400°C, and A(T) was calculated. Measurement equipment: Powder X-ray diffraction measurement equipment SmartLab (manufactured by Rigaku) X-ray generator: CuKα source, voltage 45kV, current 200mA Slit: Slit width 2mm Scan step: 0.02deg Scan range: 5-80deg Scan speed: 10deg / min X-ray detector: One-dimensional semiconductor detector Sample preparation: Powderization by mortar grinding Measurement atmosphere: Ar 100mL / min Sample stage: Dedicated glass substrate made of SiO2 The titanium oxides of Examples 1 to 5 and Comparative Examples 1 to 3 all had diffraction peaks attributable to Ti2O3 of the corundum structure space group R-3c.

[0105] <Evaluation of thermal expansion control properties> The thermal expansion control property was evaluated by the following method. The linear thermal expansion coefficient of the obtained sintered body (molded body) sample of titanium oxide was measured using the following device. Measurement equipment: Thermo plus EVO2 TMA series Thermo plus 8310 Temperature range: 25℃-320℃ Reference solid: Alumina A typical size of the sintered sample was 15 mm x 4 mm x 4 mm. For a sintered body of 15 mm × 4 mm × 4 mm, the sample length L (T) at temperature T was measured, with the longest side being the sample length L. The dimensional change rate ΔL (T) / L (30 °C) relative to the sample length at 30 °C (L (30 °C)) was calculated by the following formula. ΔL(T) / L(30℃)=(L(T)-L(30℃)) / L(30℃) In the range of 40°C to 300°C, the dimensional change rate ΔL(T) / L(30°C) was linearly approximated as a function of T from (T-10°C) to (T+10°C) using the least squares method, and the slope of the linear approximation was defined as the coefficient of linear thermal expansion α(1 / °C) at temperature T°C. The coefficient of linear thermal expansion at each temperature was determined to have the largest absolute value of the negative coefficient of linear thermal expansion and the temperature at that time. A material was evaluated as being good when the temperature at which the coefficient of linear thermal expansion had the largest absolute value of the negative coefficient of linear thermal expansion was lower than 190°C.

[0106] <Evaluation of oxygen vacancy amount δ> The amount of oxygen vacancy δ was evaluated by thermogravimetric analysis of each titanium oxide in Examples 1 to 5 and Comparative Examples 1 and 2. Assuming that the oxidation reaction of titanium oxide proceeds by thermogravimetric analysis, the amount of oxygen vacancy δ was calculated according to the following formula (1). The titanium oxide after the oxidation reaction is called the final oxide. Measurement equipment: Thermogravimetric analyzer TGDTA6300AST-2 (manufactured by SII Nano Technology Co., Ltd.) Heating program: Raise temperature from 30°C to 100°C at 10°C / min, hold at 100°C for 5 minutes, then raise temperature from 100°C to 1300°C at 10°C / min, hold at 1300°C for 10 minutes. Measurement atmosphere: dry air 200mL / min

number

[0107] In formula (1), M F was calculated based on the oxidation state of each contained metal at 1300℃ after standardizing the sum of the coefficients of the composition formula of Ti and metal or semimetal elements other than Ti for each titanium oxide feed composition to 1. Ti was oxidized to TiO2, Nb to Nb2O5, Al to Al2O3, Cr to Cr2O3, and Si to SiO2, and the calculation was made for a mixture of these. In Example 1, (0.935TiO2+0.0325Nb2O5) was used as the final oxide. F was calculated. In Example 2, (0.90TiO2+0.05Al2O3) was used as the final oxide, and M F was calculated. In Example 3, (0.915TiO2 + 0.0425Cr2O3) was used as the final oxide. F was calculated. In Example 4, (0.95TiO2+0.025Cr2O3) was used as the final oxide. F was calculated. In Example 5, (0.875TiO2+0.0625Nb2O5) was used as the final oxide. F was calculated. In Comparative Example 1, TiO2 was used as the final oxide. F was calculated. In Comparative Example 2, (0.995TiO2+0.005SiO2) was used as the final oxide, and M F was calculated.

[0108] In Example 1, (0.935Ti+0.065Nb) is used as M I It was calculated as: In Example 2, (0.90Ti+0.10Al) was used as M. I It was calculated as: In Example 3, (0.915Ti+0.085Cr) is used as M I It was calculated as: In Example 4, (0.95Ti+0.05Cr) is used as M I It was calculated as: In Example 5, (0.875Ti+0.125Nb) was used as M I It was calculated as: In Comparative Example 1, the atomic weight of Ti is M I It is. In Comparative Example 2, (0.995Ti+0.005Si) was used as M I It was calculated as:

[0109] <Example 1> 5.53 g of Ti2O3 powder (Kojundo Chemical Co., Ltd., 150 μm pass, purity 99.9%) and 0.47 g of Nb2O3 powder (Kojundo Chemical Co., Ltd., Grain, 2-5 mm, purity 99.9%) were weighed and crushed in a mortar to obtain a first mixed powder. The obtained first mixed powder was packed into a dedicated carbon die and subjected to spark plasma sintering under the following conditions to obtain a first sintered body.

[0110] Equipment: Doctor Sinter Lab SPS-511S (manufactured by Fuji Electric Industries Co., Ltd.) Sample: Mixed powder 6.0g Die: Carbon die made exclusively for the device, inner diameter 20mmφ Atmosphere: Argon 0.05MPa Pressure: 40MPa (12.8kN) Heating: 1500℃, 10 minutes

[0111] The first sintered body obtained was pulverized in a mortar to obtain a first titanium oxide powder. 5.56 g of the first titanium oxide powder was weighed, and 0.10 g of Ti powder (manufactured by Kojundo Chemical Co., Ltd., 300 μm pass, purity 99.95%) and 0.17 g of Nb2O3 powder (manufactured by Kojundo Chemical Co., Ltd., grain, 2-5 mm, purity 99.9%) were weighed and pulverized in a mortar to obtain a second mixed powder. The obtained second mixed powder was packed into a dedicated carbon die and subjected to spark plasma sintering under the following conditions to obtain the sintered body of Example 1. As a result of crystal structure analysis of the obtained sintered body of Example 1, A (25°C) was 0.3773 and A (100°C) was 0.3756. From the amount of charge, the charge composition of the sintered body of Example 1 was Ti 1.87 Nb 0.13 O 2.92 It is.

[0112] Equipment: Doctor Sinter Lab SPS-511S (manufactured by Fuji Electric Industries Co., Ltd.) Sample: Mixed powder 6.0g Die: Carbon die made exclusively for the device, inner diameter 20mmφ Atmosphere: Argon 0.05MPa Pressure: 40MPa (12.8kN) Heating: 1350℃, 10 minutes

[0113] <Example 2> 3.71 g of Ti2O3 powder (Kojundo Chemical Co., Ltd., 150 μm Pass, purity 99.9%) and 0.29 g of Al2O3 powder (Kojundo Chemical Co., Ltd., average particle size approximately 1 μm, purity 99.9%) were weighed out and pulverized in a mortar to obtain a mixed powder. The obtained mixed powder was packed into a dedicated carbon die and subjected to spark plasma sintering under the following conditions to obtain a sintered body of Example 2. As a result of crystal structure analysis of the obtained sintered body of Example 2, A (25°C) was 0.3772. From the amounts of the materials charged, the composition of the sintered body of Example 2 was Ti 1.80 Al 0.20 It is O3.

[0114] Equipment: Doctor Sinter Lab SPS-511S (manufactured by Fuji Electric Industries Co., Ltd.) Sample: Mixed powder 4.0g Die: Carbon die made exclusively for the device, inner diameter 20mmφ Atmosphere: Argon 0.05MPa Pressure: 40MPa (12.8kN) Heating: 1500℃, 10 minutes

[0115] <Example 3> 5.46 g of Ti2O3 powder (Kojundo Chemical Co., Ltd., 150 μm Pass, purity 99.9%) and 0.54 g of Cr2O3 powder (Kojundo Chemical Co., Ltd., average particle size 3 μm, purity 99.9%) were weighed out and pulverized in a mortar to obtain a mixed powder. The obtained mixed powder was packed into a dedicated carbon die and subjected to spark plasma sintering under the conditions of Example 2, except that the amount of mixed powder was changed to 6.0 g, to obtain a sintered body of Example 3. The crystal structure analysis of the obtained sintered body of Example 3 showed that A(25°C) was 0.3769 and A(100°C) was 0.3761. From the amounts of the materials charged, the composition of the sintered body of Example 3 was Ti 1.83 Cr 0.17 It is O3.

[0116] <Example 4> 3.79 g of Ti2O3 powder (Kojundo Chemical Co., Ltd., 150 μm Pass, purity 99.9%) and 0.21 g of Cr2O3 powder (Kojundo Chemical Co., Ltd., average particle size approximately 3 μm, purity 99.9%) were weighed out and pulverized in a mortar to obtain a mixed powder. The obtained mixed powder was packed into a dedicated carbon die and subjected to spark plasma sintering under the conditions of Example 2, except that the heating temperature was changed to 1300°C, to obtain a sintered body of Example 4. As a result of crystal structure analysis of the obtained sintered body of Example 4, A (25°C) was 0.3772. From the amount of charge, the charge composition of the sintered body of Example 4 was Ti 1.90 Cr 0.10 It is O3. <Example 5> 4.75 g of Ti2O3 powder (Kojundo Chemical Co., Ltd., 150 μm pass, purity 99.9%), 0.10 g of Ti powder (Kojundo Chemical Co., Ltd., 300 μm pass, purity 99.95%), and 1.14 g of Nb2O3 powder (Kojundo Chemical Co., Ltd., Grain, 2-5 mm, purity 99.9%) were weighed and crushed in a mortar to obtain a mixed powder. The obtained mixed powder was packed into a dedicated carbon die and subjected to spark plasma sintering under the conditions of Example 2, except that the heating temperature was changed to 1350°C, to obtain a sintered body of Example 5. As a result of crystal structure analysis of the obtained sintered body of Example 5, A(25°C) was 0.3758 and A(100°C) was 0.3752. From the amount of charge, the charge composition of the sintered body of Example 5 was Ti 1.75 Nb 0.25 O 2.92 It is.

[0117] <Comparative Example 1> 6.60 g of Ti2O3 powder (manufactured by Kojundo Chemical Co., Ltd., 150 μm Pass, purity 99.9%) was pulverized in a mortar to obtain a powder. The obtained powder was packed into a dedicated carbon die and subjected to spark plasma sintering under the conditions of Example 2, except that the powder amount was 6.60 g and the heating temperature was changed to 1350°C, to obtain a sintered body of Comparative Example 1. As a result of crystal structure analysis of the obtained sintered body of Comparative Example 1, A(25°C) was 0.3779 and A(100°C) was 0.3770. From the amount of charge, the charge composition of the sintered body of Comparative Example 1 was Ti2O3.

[0118] <Comparative Example 2> 1.00 g of Ti powder (Kojundo Chemical Co., Ltd., 300 μm pass, purity 99.95%) 6.00 g of TiO2 powder (manufactured by Kojundo Chemical Co., Ltd., average particle size approximately 2 μm, purity 99.99%) and 0.03 g of SiO2 powder (manufactured by Kojundo Chemical Co., Ltd., average particle size 0.8 μm, purity 99.9%) were weighed out and crushed in a mortar to obtain a mixed powder. The obtained mixed powder was packed into a dedicated carbon die and subjected to spark plasma sintering under the conditions of Example 2, except that the mixed powder amount was 6.0 g, the heating temperature was 1100°C, and the sintering time was 45 minutes, to obtain a sintered body of Comparative Example 2. As a result of crystal structure analysis of the obtained sintered body of Comparative Example 2, A (25°C) was 0.3786. From the amount of charge, the charge composition of the sintered body of Comparative Example 2 was Ti1.99 S 0.01 O 3.14 It is.

[0119] <Comparative Example 3> 1.96 g of Ti2O3 powder (Kojundo Chemical Co., Ltd., 45 μm Pass, purity 99%), 2.23 g of Cr2O3 powder (average particle size about 3 μm, purity 99.9%), and 1.96 g of ZrO2 powder (Kojundo Chemical Co., Ltd., particle size 20-40 μm, purity 98%) were weighed and crushed in a mortar to obtain a mixed powder. The obtained mixed powder was packed into a dedicated carbon die and subjected to spark plasma sintering under the conditions of Example 2, except that the amount of mixed powder was 6.0 g, the heating temperature was 1200°C, and the sintering time was 1 hour, to obtain a sintered body of Comparative Example 3. As a result of crystal structure analysis of the obtained sintered body of Comparative Example 2, A (25°C) was 0.3711. From the amount of charge, the charge composition of the sintered body of Comparative Example 3 was Ti 0.72 Cr 0.77 Zr 0.38 It is O3.

[0120] The results obtained for the examples and comparative examples are shown in Table 1. [Table 1]

[0121] FIG. 1 shows the temperature dependence of the dimensional change rate ΔL(T) / L (30° C.) for Examples 1, 2, and 5 and Comparative Examples 1, 2, and 3.

[0122] FIG. 2 shows the linear thermal expansion coefficient α(T) (1 / ° C.) of Examples 1 to 5 and Comparative Examples 1, 2 and 3, that is, the temperature derivative of the dimensional change rate ΔL(T) / L (30° C.).

[0123] FIG. 3 shows the relationship between temperature and A(T) in Examples 1 and 5 and Comparative Example 1.

[0124] It was confirmed that the titanium oxide of the example exhibited a maximum absolute negative coefficient of linear thermal expansion at a temperature lower than 190°C.

Claims

1. A titanium oxide that satisfies the following requirements 1 to 3: The titanium oxide is Ti 2-x M x O 3-δ (x = 0.02 to 0.66, δ = -0.32 to 0.40) (wherein M is a metal and / or semimetal element other than titanium), M is at least one selected from the group consisting of Al, Cr, and Nb. Requirement 1: A(T) is less than 0.3780 at T = 25°C. A(T) is (lattice constant of the a-axis (short axis) of the titanium oxide) / (lattice constant of the c-axis (long axis) of the titanium oxide) at temperature T, and each of the lattice constants is obtained from X-ray diffraction measurement of the titanium oxide. Requirement 2: Contains metal and / or metalloid elements other than titanium. Requirement 3: The total molar content of metal and metalloid elements other than titanium is equal to or less than the molar content of titanium.

2. 2. The titanium oxide according to claim 1, wherein A(T) is 0.3774 or less at T = 25°C.

3. 3. The titanium oxide powder according to claim 1 or 2.

4. A powder composition comprising the powder according to claim 3.

5. A solid composition comprising the powder according to claim 3 or the powder composition according to claim 4.

6. A liquid composition comprising the powder according to claim 3 or the powder composition according to claim 4.

7. A molded product of the powder according to claim 3 or the powder composition according to claim 4.

Citation Information

Patent Citations

  • Method of preparing composite titanium oxide

    JP2010120817A

  • Method for producing perovskite type compound oxide powder

    JP2012140309A

  • Method for synthesizing reduction type titanium oxide

    JP2012214348A

  • Active material for lithium secondary batteries, manufacturing method thereof, and lithium secondary battery arranged by use thereof

    JP2015187936A

  • Titanium oxide and method for producing the same, active material for secondary battery and method for producing the same, and secondary battery with titanium oxide used as active material

    JP2016030698A